2014
DOI: 10.3389/fneur.2014.00173
|View full text |Cite
|
Sign up to set email alerts
|

Divergent Temporal Expression of Hyaluronan Metabolizing Enzymes and Receptors with Craniotomy vs. Controlled-Cortical Impact Injury in Rat Brain: A Pilot Study

Abstract: Traumatic brain injury (TBI) triggers many secondary changes in tissue biology, which ultimately determine the extent of injury and clinical outcome. Hyaluronan [hyaluronic acid (HA)] is a protective cementing gel present in the intercellular spaces whose degradation has been reported as a causative factor in tissue damage. Yet little is known about the expression and activities of genes involved in HA catabolism after TBI. Young adult male Sprague-Dawley rats were assigned to three groups: naïve control, cran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
28
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(29 citation statements)
references
References 104 publications
1
28
0
Order By: Relevance
“…In line with these findings, gene expression for hyaluronan synthases (HAS1) and HAS2, which catalyze the production and extracellular release of hyaluronan, was increased in the ipsilateral brain at 1–3 days post-TBI [142]. Hyaluronidase 1 (HYAL1) also was increased in the contralateral hemisphere at 1–3 days post-TBI [142] whereas expression of the HA receptor, CD44, was dramatically increased around the contusion for up to one week post-TBI [142].…”
Section: Damage Associated Molecular Patterns (Damps): Mediators Omentioning
confidence: 77%
See 1 more Smart Citation
“…In line with these findings, gene expression for hyaluronan synthases (HAS1) and HAS2, which catalyze the production and extracellular release of hyaluronan, was increased in the ipsilateral brain at 1–3 days post-TBI [142]. Hyaluronidase 1 (HYAL1) also was increased in the contralateral hemisphere at 1–3 days post-TBI [142] whereas expression of the HA receptor, CD44, was dramatically increased around the contusion for up to one week post-TBI [142].…”
Section: Damage Associated Molecular Patterns (Damps): Mediators Omentioning
confidence: 77%
“…In line with these findings, gene expression for hyaluronan synthases (HAS1) and HAS2, which catalyze the production and extracellular release of hyaluronan, was increased in the ipsilateral brain at 1–3 days post-TBI [142]. Hyaluronidase 1 (HYAL1) also was increased in the contralateral hemisphere at 1–3 days post-TBI [142] whereas expression of the HA receptor, CD44, was dramatically increased around the contusion for up to one week post-TBI [142]. Moreover, a recent genome wide sequencing study from perilesional cortex, thalamus, and hippocampus at three months post-TBI separately revealed a similar upregulation of CD44 after TBI [131], suggesting a dynamic regulation and role for HA metabolism after TBI; however, the precise functions and therapeutic potential of HA remains poorly defined after CNS injury.…”
Section: Damage Associated Molecular Patterns (Damps): Mediators Omentioning
confidence: 77%
“…PH20 was also reported to be present, albeit at low levels, in the rat brain in a study on traumatic brain injury 6. These studies found PH20 in the brain, under certain conditions, using both antibody‐based techniques and PCR.…”
mentioning
confidence: 89%
“…Another role of HA in TBI pathophysiology is through the degradation of HA into small fragments by injury-associated reactive oxygen species (Soltes et al 2006) and activation of the HA degrading enzyme hyaluronidase (Xing et al 2014). Hyaluronan fragments are biologically active, and can modulate the immune response and promote angiogenesis (Stern et al 2006).…”
Section: Other Ecm Componentsmentioning
confidence: 99%